Angiotensin type-2 (AT-2)-receptor activation reduces renal fibrosis in cyclosporine nephropathy: evidence for blood pressure independent effect. Issue 6 (3rd November 2016) - Castoldi, Giovanna; di Gioia, Cira R.T.; Carletti, Raffaella; Roma, Francesca; Zerbini, Gianpaolo; Stella, Andrea
Abstract : Compound 21 (C21), selective agonist of angiotensin type-2 (AT-2) receptors, shows anti-inflammatory effects in experimental models of hypertension and nephroprotection in diabetes. The aim of the present study was to evaluate the effects of C21 in cyclosporine nephropathy, which is characterized mainly by tubulo-interstitial fibrosis. Ten days before and during the experimental periods, low-salt diet was administered to Sprague–Dawley rats. Cyclosporine-A (CsA; 15 mg/kg per day, intraperitoneal injection) and CsA plus C21 (0.3 mg/kg per day, intraperitoneal injection) were administered for 1 and 4 weeks. Control groups were left without any treatment. Blood pressure (plethysmographic method) and 24 h urinary albumin excretion were measured once a week. At the end of the experimental protocols, the kidneys were excised for histomorphometric analysis of renal fibrosis and for immunohistochemical evaluation of inflammatory infiltrates and type I and type IV collagen expression. After 1 and 4 weeks, the rats treated with CsA showed a significant increase ( P <0.01) in blood pressure, no significant changes in urinary albumin excretion and a significant increase ( P <0.01) in glomerular and tubulo-interstitial fibrosis and inflammatory infiltrates as compared with the control rats. Treatment with C21 did not modify the CsA dependent increase of blood pressure, which was higher than in control rats, but after 4 weeks of treatment significantly reduced ( P <0.01) glomerular and tubulo-interstitial fibrosis, type 1 collagen expression and macrophage infiltration, as compared with rats treated with cyclosporine. The administration of C21 showed a protective effect on cyclosporine nephropathy, decreasing renal fibrosis and macrophage infiltration. These data suggest that C21 may counteract tubulo-interstitial fibrosis, the most potent predictor of the progression of renal diseases.